ACCULTURATION AND PSYCHOLOGICAL WELLBEING AMONG CHINESE AMERICAN OLDER ADULTS - Zheng, Z (Innov Aging, 2018)
This paper aimed to examine the relationship between acculturation and changes in psychological wellbeing over two years from the Population Study of Chinese Elderly in Chicago (PINE Study). Previous research shows that the low level of acculturation in older Chinese Americans was likely to reduce their engagement in cognitive and social activities and impact their wellbeing and quality of life. A targeted community-based recruitment strategy was implemented throughout the Greater Chicago area, and 3,157 Chinese older adults aged 60 and older were surveyed from 2011 to 2013. 2,713 completed a follow-up interview after 2 years. Acculturation was measured through 12 items from the Short acculturation scale for Hispanics. Psychological wellbeing was measured in loneliness, perceived stress, hopelessness, anxiety, and depressive symptoms. Logistic regression models were used to examine the association between acculturation and decrease, increase, and no change in psychological wellbeing. Results shows that participants with higher levels of acculturation were less likely to experience higher loneliness symptoms after two years compared to those with no change in loneliness symptoms. No statistically significant associations were found between acculturation and changes in other measures of psychological wellbeing, while existing research has found significant relationships between acculturation and psychological wellbeing. Future research should investigate the mechanism through which acculturation affects loneliness of Chinese American older adults and examine other related factors that impact their psychological wellbeing.